Effect of 1-acyl-5,6-dimethoxy / diethoxy-2-methylthiobenzimidazoles on APD90 and isometric contraction in guinea pig atrium and aortic preparations activated by carbachol and phenylephrine - GARALIENĖ, Vida; LABANAUSKAS, Linas; BRŪKŠTUS, Algirdas; BARSYS, Vygantas (Acta medica Lituanica, 2010)
Studies have shown that 1-acyl-5,6-diethoxy-2-methylthiobenzimidazole derivatives 3-pyridyl-(1); 2-pyridyl- (2); 4-thiazolyl- (3); 4-pyridyl- (4); methyl- (5); 2-thienyl- (6) and 1-acetyl-5,6-dimethoxy-2-methylthiobenzimidazole (7) exhibit positive inotropic properties.The goal of the study was to investigate the effects of the above-mentioned compounds in restoring a decreased isometric contraction and APD90 induced by carbachol in an isolated guinea pig atrium, and to relax the aortic rings precontracted by phenylephrine.Isometric contraction and APD90 were recorded by using a force transducer and standard microelectrode technique (stimulation rate 1 Hz).Carbachol (1 μM) caused a decrease of the isometric contraction and APD90 on an overage by 63.2% and 49.6%, respectively. Compounds 1–5 used in a dose-dependent fashion (10–500 μM) abolished the action of carbachol and restored the contraction force and APD90 in the electrically driven atrium significantly; compound 2 reversed the APD90 to the baseline. Compounds 2 and 7 antagonized the contraction of aortic rings evoked by phenylephrine (10–4 M) and caused their relaxation by 24.4% and 17% at a dose of 10–4 M and by 76.2% and 72.5% at a dose of 5 × 10–4 M in groups 2 and 7, respectively.Conclusion. The results presented in the study have shown that some 1-acyl-5,6-dimethoxy / diethoxy-2-methylthiobenzimidazoles are able to abolish the effects of carbachol and phenylephrine on the AP duration and isometric contraction in guinea pig atrium and blood vessels. These data will contribute to the synthesis of targeted compounds with positive inotropic and blood-vessel relaxing characteristics among benzimidazole derivatives, which could be useful in clinical practice.Keywords: 1-acyl-2-methylthio-5,6-dimethoxy / diethoxybenzimidazoles, guinea pig atrium, blood vessel, phenylephrine hydrochloride, carbamylcholine chloride